2023
DOI: 10.1007/s11356-023-27320-7
|View full text |Cite
|
Sign up to set email alerts
|

Random forest regression on joint role of meteorological variables, demographic factors, and policy response measures in COVID-19 daily cases: global analysis in different climate zones

Abstract: Different sources of factors in environment can affect the spread of COVID-19 by influencing the diffusion of the virus transmission, but the collective influence of which has hardly been considered. This study aimed to utilize a machine learning algorithm to assess the joint effects of meteorological variables, demographic factors, and government response measures on COVID-19 daily cases globally at city level. Random forest regression models showed that population density was the most crucial determinant for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 82 publications
(76 reference statements)
5
3
0
Order By: Relevance
“…There was a nonlinear relationship between ambient temperature and morbidity. We found that the threshold was around 10–25 °C, which is similar to other global studies 70 , 77 . Recognizing a specific temperature threshold can serve as a triggering factor for early warning of COVID-19 78 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…There was a nonlinear relationship between ambient temperature and morbidity. We found that the threshold was around 10–25 °C, which is similar to other global studies 70 , 77 . Recognizing a specific temperature threshold can serve as a triggering factor for early warning of COVID-19 78 .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the importance of relative humidity ranks last among all meteorological variables, indicating that relative humidity may be a secondary determinant of local transmission of COVID-19. Similar findings have also been concluded in epidemiological studies 70 . The results show that in continental areas, the impact of relative humidity on the spread of COVID-19 exhibits a "U" shape, which is consistent with other studies 70 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations